EFFECTIVENESS OF JOGING AND SWIMMING TRAINING ON MAXIMUM OXYGEN VOLUME IMPROVEMENT (VO₂ MAX) IN ADOLESCENT MEN - Abdurrasyid,; Padafani, Yohanis; Wahyuddin,; Eka Sumadhinata, Yelli (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To determine the effectiveness of exercise jogging and swimming to increase the maximum volume of oxygen (VO₂ max) on adolescents. Methods: This study is an experimental study to determine the effects of interventions to research object. The sample consisted of 24 students (adolescents aged 17-25 years) and are selected based on purposive sampling technique to use your table parq assessment tests (Physical Activity Readiness Questionnaire) available. Samples were divided into two treatment groups, ie the first treatment group consisted of 12 people with a given practice jogging, while the treatment group II consisted of 12 people with a given swimming. Results: hypothesis testing in treatment I mean before it was 36,093 ± 0,518, after the average was 39,876 ± 0,544 with related t-test p value = 0,001 which means jogging exercise can improve VO₂ max on adolescents. On average before treatment II was 36,160 ± 0,580, after the average was 40,820 ± 0,434 with related t-test p value = 0,001 which means the swimming exercises can improve VO₂ max on adolescents. III hypothesis testing I mean treatment was 3,796 ± 0,193, mean treatment II was 4,743 ± 0,364 with independent t-test showed the value of 0,187, which means there are differences increase VO₂ max on adolescents. Conclusions: Exercise jogging and swimming are effective in improving VO₂ max on adolescents. However, swimming exercises better in improving VO₂ max on adolescents.